On Numerical Methods for Robust Pole Assignment in Control System Design (Journal of Computational Mathematics, 1987)
It is known that selection of a well-conditioned set of vectors from given subspaces is the key step for solving the robust pole assignment problem. In this paper we suggest two numerical methods for selecting such set of vectors. The numerical methods, Method (I) and Method (II), are described, and some numerical results are presented.